The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12961-022-00887-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the scalability of a health management-strengthening intervention at the district level: a qualitative study in Ghana, Malawi and Uganda

Abstract: Background The scale-up of successfully tested public health interventions is critical to achieving universal health coverage. To ensure optimal use of resources, assessment of the scalability of an intervention is recognized as a crucial step in the scale-up process. This study assessed the scalability of a tested health management-strengthening intervention (MSI) at the district level in Ghana, Malawi and Uganda. Methods Qualitative interviews we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 20 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…The emergent approach entails a dynamic, flexible or adaptable process that emerges from stakeholders’ interactions. We found that most CBP approaches were prescribed and collective,4 9 19 47 67 70 72 75–79 81 84 85 87 89–93 95–100 103 105 and prescribed and individual 17 68 69 71 73 80 82 83 86 94 101 102. The emergent and collective approach was marginal9 49 (figure 4).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The emergent approach entails a dynamic, flexible or adaptable process that emerges from stakeholders’ interactions. We found that most CBP approaches were prescribed and collective,4 9 19 47 67 70 72 75–79 81 84 85 87 89–93 95–100 103 105 and prescribed and individual 17 68 69 71 73 80 82 83 86 94 101 102. The emergent and collective approach was marginal9 49 (figure 4).…”
Section: Resultsmentioning
confidence: 91%
“…Weak leadership and/or management were considered the major causes of poor health outcomes in low-income and middle-income countries 4 6 19 49 67–88. Frequently mentioned causes of weak leadership and/or management capacity were (1) inadequate professional profiles of health managers (often being clinicians without formal training on leadership and management)17 73 75 81 89 90 and (2) inadequate efficacy of leadership and management courses (usually classroom-based and knowledge-focused instead of practice-based and providing know-how to deal with real-life situations) 47 68 69 73 74…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this last element, the different elements of the framework come together, as the scale-up strategy should contain strategic choices concerning dissemination and advocacy, organizational processes, cost and resource mobilization, and monitoring and evaluation. In the context of PERFORM2Scale, the innovation is the management strengthening intervention, which proved to be a scalable intervention based on an assessment of the scalability of the intervention [ 10 ]. The user organization in Uganda is the Ministry of Health (MoH), in Malawi it is the MoH and the Ministry of Local Government, and in Ghana it is the MoH and the Ghana Health Service.…”
Section: Introductionmentioning
confidence: 99%